Benefits of complementing eye-tracking analysis with think-aloud protocol in a multilingual country with high power distance - Sivaji, A. (Springer International Publishing, 2014)
This chapter is based on a research conducted that involves usability testing on websites performed on a target audience that are multilingual (English, Malay, Mandarin and Tamil). If a study is carried out without an eye tracker, the moderator has to rely on the think-aloud (TA) feedback and the notes captured by the usability analyst. Moreover, it has been found that using TA technique alone may not be suitable and reliable in usability studies in Malaysia whereby there exists high power distance (Hofstedeâs model). With the eye tracker, the usability practitioner can now complement the TA feedback with one of the human biometric feature, which in this case is the userâs eye. This increases the data integrity obtained from all users. Using a combination of visualisation and analysis tools from the Tobii Studio such as cluster plot and gaze data, areas of high concentration in a web interface could be revealed. Based on the marked areas of interest (AOI), descriptive statistics such as fixation count, fixation duration, time to first fixation and mouse click-related data were used to correlate with the data obtained from the TA protocol. For instance, the consistent results from the TA and eye tracking enabled the moderator to conclude that one website had more efficient navigation strategy than other. There was a significant correlation and consistency between the TA feedback and the eye-tracking analysis. This enabled the usability analyst to present the findings with visual, audio and statistical evidence, eventually increasing the persuasive power towards the design and development team to implement changes. The findings of this study challenges the recruitment criteria spelt out in user experience (UX) studies today which limits the subjects to the language of the website being tested. Â© Springer International Publishing Switzerland 2014.